Application of the current diagnostic algorithm for early mycosis fungoides to a single center cohort: Identification of challenges and suggestions for modification. (6th June 2022) - Krishnasamy, Shalini; Correia, Emily; Kartan, Saritha; Wang, Xuejun; Porcu, Pierluigi; Cha, Jisun; Nikbakht, Neda
Abstract: Background: Diagnosing early‐stage mycosis fungoides (MF) remains a significant challenge. The International Society for Cutaneous Lymphomas (ISCL) proposed an algorithm for diagnosing early MF incorporating clinical and histopathologic characteristics, as well as immunohistochemistry and molecular studies. Here we aim to examine the diagnostic utility of the ISCL algorithm. Methods: In this single‐center retrospective review, the ISCL algorithm was applied to 28 patients diagnosed with early‐stage MF. Immunohistochemistry and molecular studies were not performed for all patients, so a subgroup analysis was conducted including 18 patients in whom both studies had been performed. We calculated the diagnostic sensitivity of the algorithm. Subsequently, we examined how modifying the algorithm's histopathologic criterion from epidermotropism without spongiosis to epidermotropism influenced its sensitivity. Results: Forty‐three percent (12/28) of the cohort and 50% (9/18) of the subgroup met the algorithm's diagnostic threshold. When the algorithm was modified, 71% of the cohort and 89% of the subgroup met the algorithm's threshold. Conclusion: While the ISCL algorithm is useful in diagnosing early‐stage MF, its sensitivity remains suboptimal. Further refinement of the algorithm to capture spongiotic subtypes of MF may improve its diagnostic value.